Master of five excellences - Cheng, Man-ch'ing 1902-1975 (Frog, Ltd. Distributed by North Atlantic Books, 1995)
Professor Cheng Man-Ch'ing regarded a set of five disciplines - the "five excellences" - to be the mark of a well-rounded person: calligraphy, painting, poetry, t'ai chi, and medicine. Although he is best known for his teachings on the martial arts (in particular, his highly influential adaptation of t'ai chi), versatility was central to Cheng's philosophy of life, and he encouraged his students to combine artistry with scholarship. This inspiring book is a commentary on and working compendium of Cheng's literary and pictorial interpretations of these subjects. Full-color reproductions of Cheng's own calligraphic compositions and paintings - some of which hang in the collections of the National Palace Museum in Taiwan - reveal his visual creativity. Another chapter is based on commentary and analysis of the I Ching. To Cheng, it was the blending of philosophy, art, and action that made t'ai chi a worthy lifelong pursuit, and Hennessy's commentaries and translations illuminate this concept. Of interest to aficionados of Chinese art, culture, and history, Master of Five Excellences also offers internal techniques for practitioners of the martial arts, as Hennessy provides an insight into the rarely-glimpsed creative side of Cheng Man-Ch'ing.